Tributação e desigualdades de gênero e raça: vieses de gênero na tributação sobre produtos ligados ao trabalho de cuidado e à fisiologia feminina - Luiza Machado de Oliveira Menezes (2023)
This work intends to investigate the relationship between indirect taxation and gender and race inequalities in Brazil. First, it is necessary to analyze whether regressivity, in addition to increasing income inequality, also has impacts on gender and racial inequalities. Second, to investigate whether taxation on products related to care work and linked to female physiology constitutes implicit gender discrimination in the national tax system. The research hypothesis is that women are more affected by taxation, compared to men, due to regressivity and taxation on products related to care work and female physiology.